Toward geomorphometry of plains - Country-level unsupervised classification of low-relief areas (Poland) - Dyba, Krzysztof; Jasiewicz, Jarosław (My University, 2022)
Low-relief areas are not fully the main subject of geomorphometric analyses. The development of the automatic classification of landforms mainly focuses on landforms related to the fluvial morphogenetic cycle. Thus, the morphogenetic diversity of the plains is not reflected in the existing classification systems. The area of Poland where the low relief area exceeds 80 % of the country's territory and results in various morphogenetic processes was selected for the analysis. The purpose of the analysis was recognition of the differentiation of surface types. The first step includes selecting appropriate morphogenetic variables, the second unsupervised classification using the Gaussian Mixture Model, and the third one encompassing the interpretation, namely the labeling process. Twenty Land Surface Types were distinguished, five belonging to uplands, and the remaining 15 types of plains were divided into four subgroups: rolling plains, dissection plains, smooth plains, and near-flat plains. Compared with other classification systems, terrain forms, morphogenetic strides, and physiographic division. The comparison showed a strong correspondence between the morphogenesis of the area and the inventory of surface types, and the high consistency of the Land Surface Types patterns within physiographic units.
Keywords: Geomorphometry of plains; Gaussian Mixture Model; Surface texture; Uncertainty; Poland